Short film project Awaken: Fractured time in cinematography / Tengku Idzudin Nazrin Tengku Idris - Tengku Idris, Tengku Idzudin Nazrin (Faculty of Film, Theatre and Animation, 2014)
This study focuses on the concept of time-image in cinematography to the short film project Awaken. The concept of time-image was introduced by French philosopher Gilles Deleuze. Awaken revolves around a man, Ali who is trapped in a time repetition in order to save his wife, Debs from killing herself. The concept of time-image is commonly debated and discussed within film studies as it intends to signify the usage of ‘real time’ in cinema. This study uses the qualitative research method in order to gather data and information about Deleuze’s concept and also cinematography in filmmaking. Through cinematography, this study aims to articulate a specific ideological content that can be associated with ‘time-image’. The main aspects of cinematography are designed and manipulated in order to signify ‘time-image’ are lighting as well as camera composition. On a much deeper level, the use of ‘time-image’ is in line with the film’s narrative that tends to critique Malaysian modernity, as the concept echoes the pre-modern, heterogeneous notions of time.